The relationship between pre-harvest stress and the carcass characteristics of beef heifers that qualified for kosher designation. (February 2015) - Hayes, N.S.; Schwartz, C.A.; Phelps, K.J.; Borowicz, P.; Maddock-Carlin, K.R.; Maddock, R.J.
Abstract: Differences in pre-harvest stress measurements and carcass characteristics between kosher and not-qualified-as-kosher cattle were evaluated. Finished heifers ( n = 157) were slaughtered by a shochet while held in an upright position using Glatt slaughter procedures. Stress measurements were collected prior to slaughter. Carcass data were collected, and 3.8-cm thick samples were taken from the loin at the 13th rib. Steaks from each sample were evaluated for mechanical tenderness and simulated retail display. Cattle with shorter times from gate to exsanguination and lower vocalization scores were more likely ( P < 0.01) to qualify as kosher. Kosher carcasses had larger ( P = 0.02) ribeye areas and higher ( P < 0.0001) Warner–Bratzler shear values. At each day of simulated retail display, kosher steaks had lower ( P < 0.05) L*, a*, and b* values. These data suggest that body composition and pre-harvest stress affect the likelihood of a beef animal qualifying as kosher and quality differences exist between kosher and non-kosher steaks.